Dragon kingdom of Wrenly. Book 2, Shadow Hills - Quinn, Jordan (Little Simon, 2021)
Ruskin the dragon and his friend Cinder are sent to Shadow Hills, the most mysterious place in all of Wrenly, under false pretenses by sinister forces.